Prenatal Detection of Congenital Heart Diseases Using Echocardiography: 12-Year Results of an Improving Program With 9782 Cases - Ou, Yanqiu; Bloom, Michael S.; Mai, Jinzhuang; Francois, Melissa; Pan, Wei; Xiao, Xiaohua; Wang, Ximeng; Nie, Zhiqiang; Qu, Yanji; Gao, Xiangmin; Wu, Yong; Liu, Xiaoqing; et al. (Frontiers in Public Health, 2022)
Background A provincial program combining the effect of a government investment in prenatal screening and a specialized cardiac center was introduced in 2004, to improve prenatal diagnosis by echocardiography for congenital heart diseases (CHDs) in the Guangdong Registry of Congenital Heart Disease, China. Objectives To evaluate the effects of this program on the prenatal diagnosis rate (PDR) by echocardiography and termination of pregnancy (TOP). Methods A retrospective study from 2004-2015 included 9782 fetuses and infants diagnosed with CHDs. The PDR was calculated for major and minor CHDs during pre-, mid- and post-program time-intervals. Multivariable logistic regression was utilized to analyze the associations between program implementation and the timing of CHD diagnosis (prenatal vs. postnatal) by different hospital levels. The rate for TOP were also evaluated. Results The PDR increased by 44% for major CHDs in the post-program interval relative to the pre-program interval. The three most frequently diagnosed subtypes prenatally were hypoplastic left heart syndrome (84%), double outlet right ventricle (83%) and severe pulmonary stenosis (82%). Participants with a high school education experienced a greater increase in PDR than those without a high school education. The odds for a prenatal vs. a postnatal diagnosis for major CHD were greater after introduction of the program than before (adjusted odd ratio= 20.95, 95% CI:2.47, 178.06 in secondary hospitals; and adjusted odd ratio=11.65, 95% CI:6.52, 20.81 in tertiary hospitals). The TOP rate decreased from 52.3% pre-program to 19.6% post-program among minor CHD fetuses with a prenatal diagnosis (P for trend =0.041). A lower proportion of TOP were attributed to minor CHDs after the program. Conclusions The program combining the advantages of government investment and a specialized cardiac center appeared to increase the PDR by echocardiography for CHDs in an unselected population. The TOP rate among minor cases with prenatal diagnosis declined significantly after implementation of the program.